SIKAP MASYARAKAT TERHADAP BAHASA IBUNYA: DAYAK LENGILU, BENGGOI, DAN PAKKADO (SOCIETY ATTITUDE TOWARDS MOTHER TONGUE: DAYAK LENGILU, BENGGOI, AND PAKKADO) - Mardi Nugroho (Balai Bahasa Sulawesi Utara, 2018)
The speakers of Dayak Lengilu language are only four people in 2000. The condition of the language is almost extinct. In 1989, the speaker of Benggoi language were 350 people. According to society information, in Kecamatan Kalukku, Kabupaten Mamuju, Sulawesi Barat, there is Pakkado language which the condition is endangered. Local languages with few speakers and local languages whose condition is almost extinct or endangered should be prioritized for protection. Knowing the attitude of the society toward the local language is important in the revitalization program local languages usage. The mother tongue for most Indonesian citizens is the local language. The problem of this research is how the attitude of society toward their mother tongue, especially the Dayak Lengilu, Benggoi, and Pakkado people? The purpose of this research is to know the attitude of Dayak Lengilu, Benggoi, and Pakkado people towards their mother tongue. This research uses quantitative method. The data were collected by using questionnaire. Data processing is done quantitatively with simple statistics. Language attitude theory, measurement scale determining theories, questionnaire compiling, and questionnaire validity test theory were used in this research. The result shows that the attitude of Dayak Lengilu, Benggoi, and Pakkado language is positive. This study recommends that the results of this study can be used as a consideration in the local language protection program.